Prevalence of speech and language disorders in children in northern Kosovo and Metohija - Nešić Blagoje V.; Minić Jelena Lj.; Jakšić Aleksandra S. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2011)
On the territory of the northern part of Kosovo and Metohija (Kosovo municipalities Mitrovica, Zvecan, Leposavic and Zubin Potok) a study is conducted in primary schools in order to determine the presence of speech-language disorders in children of early school age. Data were collected from the teachers of the third and fourth grades of primary schools in these municipalities (n = 36, which include a total number of 641 student). The results show that the number of children with speech and language disorders represented in the different municipalities of the research vary (the largest is in Leposavic, the smallest is in Zvecan), then 3/4 the total number of children with speech and language disorders are boys. It is also found that the speech-language disorders usually appear from the very beginning of schooling and that the examined teachers recognize 12 types of speech-language disorders in their students. Teachers recognize dyslexia as the most common speech-language disorder, while dysphasia and distortion are the least common, in the opinion of the teachers. The results show that children are generally accepted by their peers, but only during schooling; then, there is a difference in school success between children with speech and language disorders and children without any speech-language disorders. It also found that the teachers' work is generally not affected by the children with speech and language disorders, and that there is generally an intensive cooperation between teachers and parents of children with speech and language disorders. The research and the results on prevalence of speech-language disorders in children in northern Kosovo and Metohija can be considered as an important guidelines in future work.